Sustainable Heritage Buildings: The Impact on Heritage Values, Energy Performance, and CO2 Emissions - Vieveen, Maarten; Banninga, Aron; Munuswamy, Tamizhselvan; Tineke van der Schoor (Urban planning, 2025)
The Dutch national CO2 emission targets for heritage buildings are a 60% reduction by 2040. However, holistic insights on the impact of this reduction on heritage values, energy performance, and CO2 emissions are understudied. In this article, the impact in four heritage buildings by comparing the situation before and after the renovation process was studied. These energy reduction measures were part of a larger restoration or adaptive reuse process. We used archival documentation about the original design, assessed project documentation regarding the previous technical conditions of materials, and conducted fieldwork. The data was used in a heritage assessment, focussing on cultural, historical, architectural, ensemble, authenticity, and rarity values. Energy performance and CO2 emissions were calculated based on desk research, fieldwork, and additional information provided by the owners. The CO2 emission calculations included all materials that were removed or added during the construction process. We concluded that in some cases, heritage values have been degraded by the energy reduction measures, whereas in other cases, they were improved. In all cases, we found that heritage values were lost to a certain extent. The impact on energy performance and CO2 emissions varied. CO2 emissions for operational energy were reduced by approximately 52% on average, and CO2 emissions for carbon energy were reduced by approximately 6% on average. Therefore, we conclude that energy‐efficient restoration of heritage buildings considerably reduces environmental impact but comes at a cost to heritage values.